2017
DOI: 10.1002/cptc.201700158
|View full text |Cite
|
Sign up to set email alerts
|

1,10‐Phenanthroline Ruthenium(II) Complexes as Model Systems in the Search for High‐Performing Triplet Photosensitisers: Addressing Ligand versus Metal Effects

Abstract: A series of RuII complexes containing extended 1,10‐phenanthroline ligands with triphenylamine (TPA) and/or pyrene as light‐harvesting chromophores, were synthesised and investigated in triplet photosensitising applications. “Chemistry‐on‐the‐complex” methods were employed using Sonogashira cross‐coupling reactions. Tunable absorption and triplet lifetimes were achieved depending on the type and number of the chromophores. Intense absorption in the visible region was common to the generated complexes. Those Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…[9][10][11][12][13][14] As a highly investigated class of compounds, [Ru(phen)3] 2+ derivatives have been studied as PDT PSs. [15][16][17][18] Several examples have shown that the photophysical properties, including absorption, emission as well as excited states lifetimes can be influenced by choice of the coordinated ligands. [5,9,11,13,19] Next to suitable photophysical properties, the biological abilities of a PS including, for example, cellular localisation or mechanism of cellular uptake, play a predominant role in the efficiency of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] As a highly investigated class of compounds, [Ru(phen)3] 2+ derivatives have been studied as PDT PSs. [15][16][17][18] Several examples have shown that the photophysical properties, including absorption, emission as well as excited states lifetimes can be influenced by choice of the coordinated ligands. [5,9,11,13,19] Next to suitable photophysical properties, the biological abilities of a PS including, for example, cellular localisation or mechanism of cellular uptake, play a predominant role in the efficiency of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Since the ISC is an electron spin forbidden process, the traditional triplet photosensitizers are mostly based on heavy atom effect, such as those contain Ir(III), Pt(II), Ru(II) and Os(II) transition metal ions [21][22][23][24][25][26]. However, this type of transitional photosensitizers suffer from some disadvantages, for instance, high cost of preparation, weak absorption of light in the visible region, [27,28] toxicity and short triplet lifetime (heavy atom effect can enhance the T 1 → S 0 relaxation) [29,30]. Thus, it is highly desired to design heavy atom-free triplet PSs.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Drapers Forschung über die Synthese neuartiger polyaromatischer und lumineszierender Materialien führte kürzlich zu molekularen Materialien mit hohen Quantenausbeuten für Singulett‐Sauerstoff und Aufwärtskonversion. Sie berichtete in einer Angewandte‐Chemie ‐Zuschrift über Iridium(III)‐Komplexe mit pyrenfunktionalisierten 1,10‐Phenanthrolin‐Liganden als Sensibilisatoren der Triplett‐Triplett‐Annihilierungs‐Aufwärtskonversion, und ein Beitrag ihrer Gruppe über Phenanthrolin‐Ruthenium(II)‐Komplexe als Modellsysteme für Hochleistungs‐Triplettphotosensibilisatoren wurde auf dem Titelbild von ChemPhotoChem vorgestellt.…”
Section: Ausgezeichnet …unclassified